A Low-Cost Wireless Sensor Network for Barn Climate and Emission Monitoring—Intermediate Results - Janke, David; Bornwin, Michael; Coorevits, Kobe; Hempel, Sabrina; van Overbeke, Philippe; Demeyer, Peter; Rawat, Aditya; Declerck, Arnout; Amon, Thomas; Amon, Barbara (Atmosphere, 2023)
A barn’s climate is vital for animal welfare and emissions control, including greenhouse gases like methane (CH4) and carbon dioxide (CO2) and environmental gases like ammonia (NH3). The goal of this study was to investigate a developed low-cost online tool for monitoring barn climate and air pollutant emissions (OTICE) in naturally ventilated barns. OTICE employed a wireless sensor network with low-cost sensors for gases and climate variables, allowing scalable use across multiple barns. We evaluated the sensors for CO2, NH3, and CH4 for accuracy, both in controlled lab conditions and in a dairy barn in Germany, where measurements were carried out continuously for a duration of 12 days. For the averaged concentration levels over the measurement period, the low-cost sensors agreed well with the reference system, with relative deviations lower than 7% for all three gases, with maximum peak deviations up to 32% for CO2, 67% for NH3, and 65% for CH4, with strong Spearman correlations for CO2 and NH3 (ρCO2 = 0.8, ρNH3 = 0.68) and a rather weak correlation for CH4 with ρCH4 = 0.24. Further calibration and stability investigations are required, especially for CH4 sensing. However, the overall good results for NH3 and especially CO2 measurements indicate a huge potential of the low-cost system as a valuable tool for monitoring relative NH3 emission levels and the measurement of air exchange rates in naturally ventilated barns.